Identifying Key Implication Factors to Inffuence the Approach and Promotion of the Sustainable Furniture-Sharing Platform in the Circular Economy in Bangkok, Thailand (Future Cities and Environment, 2021)
The rapid increase in the size of the population in Bangkok is one of the reasons for the swiftly increasing rate of furniture waste generated in the city which creates a significant negative impact on the socioeconomic environment. While most sharing platforms in Thailand are about sharing a ride, habitat, or hand tools; used furniture which often takes up large amounts of space in landfills is normally seldom considered as a potential value stream from the sustainability perspective. To help address this shortfall, a sustainable furniture-sharing platform that is open for all to use was designed to support sustainability practices by encouraging the use of second-hand furniture by individuals rather than them buying new. Consequently, this research investigates possible significant factors that affect the decision of likelihood of usage of the platform to widen the adoption and promotion of the sustainable sharing platform and other sustainability practices. Accordingly, the data collected via an online survey from research into developing a sustainable-sharing platform was analysed by correlation analysis to find out the relationship between possible factors. The findings provided insights which lead to four suggestions: 1) Have those in the younger generation as knowledge spreaders; 2) Have personalised channels and content for better engagement of each target group; 3) Have a reward program as an attraction for target groups who have less interest in the topic; and 4) Promoting activities that let users experience the platform is suggested to increase the likelihood of their usage of it in the future.